2001
DOI: 10.1097/00003246-200105000-00002
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized study comparing percutaneous with surgical tracheostomy in critically ill patients

Abstract: PDT is a cost-effective alternative to ST. The reduction in patient charges associated with PDT in this study resulted from the procedure being performed in the intensive care unit, thus eliminating the need for operating room facilities and personnel. PDT may become the procedure of choice for electively establishing tracheostomy in the appropriately selected patient who requires long-term mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(158 citation statements)
references
References 19 publications
5
147
0
6
Order By: Relevance
“…However, PDT was associated with a reduced incidence of wound infection (odds ratio = 0.28, 95% confidence interval, 0.16 to 0.49, P < .0005) when compared to surgical tracheostomy. 22 Other outcome measures such as costs, procedure duration, and use of minimal resources (such as materials or staff) are still controversial 2,6,19 due to methodological flaws such as selection bias (observed in nonrandomized studies 3,4,6 ) or comparisons between heterogeneous groups (such as bedside PDT versus open tracheostomy performed either bedside or in the OR 2,3,11,12 ). The advantages of a bedside procedure are demonstrated in one of the cited meta-analyses 22 ; reduced bleeding (odds ratio = 0.29, 95% confidence interval, 0.12 to 0.75, P = .01) and mortality (odds ratio = 0.71, 95% confidence interval, 0.50 to 1.0, P = .05) were observed for PDT when compared to surgical tracheostomy performed in the OR (no difference was found when compared to OBT).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, PDT was associated with a reduced incidence of wound infection (odds ratio = 0.28, 95% confidence interval, 0.16 to 0.49, P < .0005) when compared to surgical tracheostomy. 22 Other outcome measures such as costs, procedure duration, and use of minimal resources (such as materials or staff) are still controversial 2,6,19 due to methodological flaws such as selection bias (observed in nonrandomized studies 3,4,6 ) or comparisons between heterogeneous groups (such as bedside PDT versus open tracheostomy performed either bedside or in the OR 2,3,11,12 ). The advantages of a bedside procedure are demonstrated in one of the cited meta-analyses 22 ; reduced bleeding (odds ratio = 0.29, 95% confidence interval, 0.12 to 0.75, P = .01) and mortality (odds ratio = 0.71, 95% confidence interval, 0.50 to 1.0, P = .05) were observed for PDT when compared to surgical tracheostomy performed in the OR (no difference was found when compared to OBT).…”
Section: Discussionmentioning
confidence: 99%
“…It is better tolerated than oral or nasal tracheal intubation and is thought to reduce sedation requirements and time in the intensive care unit (ICU). [1][2][3][4][5][6] Traditionally, elective tracheostomy has been performed in the operating room (OR) by using the standard surgical techniques originally described by Jackson. 7 Ciaglia et al 8 described a percutaneous dilational tracheostomy (PDT) based on a model proposed by Seldinger for endovascular intervention procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective randomized study comparing PT and ST in critically ill patients, the cost of PT was found to be significantly lower (US$ 1,569±157 vs. US$ 3,172±114; P<0.0001), the duration of PT was significantly shorter (20 vs. 42 mins; P<0.0001) and there was no significant difference in the number of days intubated prior to tracheostomy or overall ICU and hospital length of stay compared to ST (65).…”
Section: Pt Versus Stmentioning
confidence: 95%
“…4). [90][91][92] On average, procedural costs for PDT are ϳ50% less than those for open surgical tracheostomy, and the reduced cost is mostly related to lack of use of the operating room and anesthesia teams. The cost difference does depend, however, on whether the open surgical tracheostomy is performed in the operating room or bedside in the ICU.…”
Section: Procedural Cost Of Tracheostomymentioning
confidence: 99%